On time : technology and temporality in modern Egypt - Barak, On (University of California Press, 2013)
In this pioneering history of transportation and communication in the modern Middle East, On Barak argues that contrary to accepted wisdom technological modernity in Egypt did not drive a sense of time focused on standardization only. Surprisingly, the introduction of the steamer, railway, telegraph, tramway, and telephone in colonial Egypt actually triggered the development of unique timekeeping practices that resignified and subverted the typical modernist infatuation with expediency and promptness. These countertempos, predicated on uneasiness over ""dehumanizing"" European standards of eff.